Computable General Equilibrium Modelling and the Evaluation of Agricultural Policy - Blake, Adam (1998)
This thesis is concerned with computable general equilibrium modelling and evaluation of agricultural policy in a global context. Particular emphasis has been given to the EU's Common Agricultural Policy, reform of which was an important element in the successful conclusion of the Uruguay Round (UR), and which is to be subject to further reforms under Agenda 2000. Nevertheless, attention has also been given to modelling the effects of other Uruguay Round outcomes in manufactures and services, so that the reform of the CAP can be assessed within the liberalised global setting.